Healthcare Utilization of Complex Chronically Ill Children Managed by a Telehealth-Based Team - Braun, Lindsay; Steurer, Martina; Henry, Duncan (Frontiers in Pediatrics, 2021)
Objectives: Medical advances have improved survival of critically ill children, increasing the number that have substantial on-going care needs. The first aim of this study was to compare healthcare utilization of children with complex chronic conditions across an extensive geographic area managed by a predominantly telehealth based team (FamiLy InteGrated Healthcare Transitions - FLIGHT) compared to matched historical controls. The second aim was to identify risk factors for healthcare utilization within the FLIGHT population. Methods We performed a retrospective cohort study of all patients enrolled in the care management team. First, we compared them to age and technology-based matched historic controls across medical resource utilization outcomes. Second, we used univariable and multivariable linear regression models to identify risk factors for resource utilization within the FLIGHT population. Results Sixty-four FLIGHT patients were included, with thirty-four able to be matched with historic controls. FLIGHT patients had significantly fewer hospital days per year (13.6 vs 30.3 days, p=0.02) and shorter admissions (6.0 days vs 17.3 days, p=0.02) compared to controls. Within the telehealth managed population, increased number of technologies was associated with more admissions per year (coefficient 0.90, CI 0.05-1.75) and hospital days per year (16.83, CI 1.76-31.90), though increased number of complex chronic conditions was not associated with an increase in utilization. Conclusion A telehealth based care coordination team was able to significantly decrease some metrics of healthcare utilization in a complex pediatric population. Future study is warranted into utilization of telemedicine for care coordination programs caring for children with medical complexity.